2008
DOI: 10.1007/s12272-001-2121-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the immune responses of mice to Bacillus anthracis protective antigen by CIA07 combined with alum

Abstract: Anthrax is an acute zoonotic disease caused by infection with Bacillus anthracis. B. anthracis spores are highly resistant to environmental degradation and are used as a biological weapon. In this study, we investigated the adjuvant activity of CIA07 to anthrax protective antigen (PA). A/J mice were immunized intraperitoneally once, or twice with a 4-week interval, with recombinant PA alone or combined with alum, CpG1826, or CIA07 as adjuvant, and serum anti-PA IgG antibody responses were measured 4 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, we observed that addition of CIA05 to a human papilloma virus (HPV) vaccine adjuvanted with alum significantly enhanced the immunogenicity of the vaccine antigen, demonstrating the synergistic activity of CIA05 and alum in the enhancement of immune responses to a vaccine antigen [18]. In a previous study, we evaluated an adjuvant effect of CIA07 to PA and observed that CIA07 alone was not as effective as alum in inducing PA-specific antibody but gave an additive effect only when combined with alum [19]. This study was carried out to evaluate the potential of CIA05 combined with alum as an adjuvant for an anthrax vaccine and to determine an optimal ratio between PA antigen, CIA05, and alum.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed that addition of CIA05 to a human papilloma virus (HPV) vaccine adjuvanted with alum significantly enhanced the immunogenicity of the vaccine antigen, demonstrating the synergistic activity of CIA05 and alum in the enhancement of immune responses to a vaccine antigen [18]. In a previous study, we evaluated an adjuvant effect of CIA07 to PA and observed that CIA07 alone was not as effective as alum in inducing PA-specific antibody but gave an additive effect only when combined with alum [19]. This study was carried out to evaluate the potential of CIA05 combined with alum as an adjuvant for an anthrax vaccine and to determine an optimal ratio between PA antigen, CIA05, and alum.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxyethylene-polyoxypropylene (POE-POP) and immunostimulatory DNA containing CpG domains, seemed to be good potentiators of PA immunogenicity in mice (111) and rhesus macaques (112). Similarly, Alum and CIA07 (a combination of bacterial DNA fragments and modified E. coli lipopolysaccharide containing a short carbohydrate chain) appeared to be superior in terms of their immunostimulatory activity, compared with each adjuvant alone, when tested in mice for PA immunization potentiation (113). The mast cell activator compound 48 ⁄ 80 also was suggested to be an efficient inducer of an anti-PA antibody responses in mice (114).…”
Section: Novel Live and Acellular Vaccinesmentioning
confidence: 99%
“…Some of these CpG motif ODNs have been evaluated in human clinical trials, thus providing a level of confi dence in their safety and effi cacy if used in human vaccines (Klinman, 2006 ). The presence of all three anthrax toxin components PA, LF, and EF in a polyvalent vaccine formulation also enhances antibody responses to all three components Kelly et al, 2007 ;Kim et al, 2008 ;Kolla et al, 2007 ;McLachlan et al, 2008 ;Park et al, 2008 ;Pezard et al, 1995 ;Quesnel -Hellmann et al, 2006 ;Sloat and Cui, 2006 ). These studies confi rm the pivotal role of PA in protection and that effi cacy can be enhanced by considered formulation, and serve as timely reminders that design of anthrax vaccines should be based fi rmly on the host in which the vaccine will eventually be used.…”
Section: Animal Models Of Effi Cacymentioning
confidence: 99%
“…This research has included analyses of PA polypeptide domains (Flick -Smith et al, 2002b ;Yan et al, 2008 ), DNA vaccines (Galloway and Baillie, 2004 ), alternative delivery technologies (Luxembourg et al, 2008 ;Mikszta et al, 2005 ), evaluation of novel adjuvants (Kelly et al, 2007 ;Kim et al, 2008 ;Park et al, 2008 ), oral and mucosal vaccines Baillie et al, 2008 ;Bielinska et al, 2007 ;Jiang et al, 2006 ;Stokes et al, 2007 ), and PA -producing liveattenuated vaccines (Ivins et al, 1990 ;Skoble et al, 2009 ).…”
Section: Anthrax Vaccine Researchmentioning
confidence: 99%